Effects of umeclidinium/vilanterol on exercise endurance in COPD: a randomised study. Issue 1 (5th January 2018) - Riley, John H.; Kalberg, Chris J.; Donald, Alison; Lipson, David A.; Shoaib, Muhammad; Tombs, Lee
This multicentre, randomised, double-blind, placebo-controlled, two-period crossover study assessed the effect of umeclidinium/vilanterol (UMEC/VI) on exercise capacity in patients with chronic obstructive pulmonary disease (COPD) using the endurance shuttle walk test (ESWT). Patients were randomised 1:1 to one of two treatment sequences: 1) UMEC/VI 62.5/25 µg followed by placebo or 2) placebo followed by UMEC/VI 62.5/25 µg. Each treatment was taken once daily for 12 weeks. The primary end-point was 3-h post-dose exercise endurance time (EET) at week 12. Secondary end-points included trough forced expiratory volume in 1 s (FEV1 ) and 3-h post-dose functional residual capacity (FRC), both at week 12. COPD Assessment Test (CAT) score at week 12 was also assessed. UMEC/VI treatment did not result in a statistically significant improvement in EET change from baseline at week 12 versus placebo (p=0.790). However, improvements were observed in trough FEV1 (206 mL, 95% CI 167–246), 3-h post-dose FRC (−346 mL, 95% CI −487 to −204) and CAT score (−1.07 units, 95% CI −2.09 to −0.05) versus placebo at week 12. UMEC/VI did not result in improvements in EET at week 12 versus placebo, despite improvements in measures of lung function, hyperinflation and health status. Umeclidinium/vilanterol: no significant improvements in exercise endurance in COPD versus placebo after 12 weeks http://ow.ly/tc9i30gudVc